PEMBELAJARAN VOKAL DENGAN METODE SOLFEGIO PADA PADUAN SUARA GRACIA GITASWARA DI GKJ CILACAP UTARA KABUPATEN CILACAP (Jurnal Seni Musik, 2015)
The research of abstract is based on the activity of learning vocal; using the solfegio methodology at Gracia Gitaswara Choir for GKJ north of Cilacap. It means that the trainer of choir should have interesting and easier methods for all the choir members to learn vocal. The aim of this research is used for knowing the plan of learning vocal, the mechanism of vocal study and factors that related to vocal learning. The research methodology is based on persuading the qualitative descriptive research. It means describe, explain in details and analyst the subjects which is studied. The result of the research shows that the application of vocal study; using solfegio methodology is an efficient and effective strategy to interest the choir members in vocal study.